Contribution of gut bacteria to liver pathobiology - Son, Gakuhei; Kremer, Michael; Hines, Ian N. (Gastroenterology research and practice, 2010)
Emerging evidence suggests a strong interaction between the gut microbiota and health and disease. The interactions of the gut microbiota and the liver have only recently been investigated in detail. Receiving approximately 70% of its blood supply from the intestinal venous outflow, the liver represents the first line of defense against gut-derived antigens and is equipped with a broad array of immune cells (i.e., macrophages, lymphocytes, natural killer cells, and dendritic cells) to accomplish this function. In the setting of tissue injury, whereby the liver is otherwise damaged (e.g., viral infection, toxin exposure, ischemic tissue damage, etc.), these same immune cell populations and their interactions with the infiltrating gut bacteria likely contribute to and promote these pathologies. The following paper will highlight recent studies investigating the relationship between the gut microbiota, liver biology, and pathobiology. Defining these connections will likely provide new targets for therapy or prevention of a wide variety of acute and chronic liver pathologies.
Gesehen am 15.09.2023